The Upshot of Key Words Technique:Descriptive Writing of English Learners - Andi Sadapotto; Nicodemus Bisse (Universitas Muhammadiyah Enrekang, 2021)
The objective of this article is to describe the upshot students descriptive writing at eleventh grade in SMA Muhammadiyah Rappang. This research employed the method of the research was pre-experimental method with one group pre-test and post-test design. The population was the Eleventh grade students (XI) of SMA Muhammadiyah Rappang in 2015-2016 academic years. Totalnumber of population was 20 students and the sample was taken by using census sampling technique, whole students at eleventh grade (20) was chosen as a sample. The instrument used in this research was to write decriptive composition. The result of this research showed that the pre-test got the mean score (53.60) while the post-test got mean score (77.95). This showed that there was significant difference between pre test and post-test. The result of the p-value (0.00) was lower than alpha (0.05). This means that H1 was accepted . the reserch concluded that teaching writing by using keyword increased the students’ ability to write descriptive composition at eleventh grade in SMA Muhammadiyah Rappang.